Phenomenon of creativity in the context of historical dynamics of socio–cultural development (the West European context) - Chumachenko, H. (Культура народов Причерноморья, 2014)
The article deals with the problem of phenomenon of creation in the context of historical dynamics of
socio–cultural development (the West European context). The emphasis is laid on importance investigation of
phenomenon of creative activity as means of search of new forms of self–expression of human activity, and the
definition of creativity as form of interconnection between different cultural–information channels. With the help
of analyses of separate concepts of creativity we traced the transition from homogeneous to heterogeneous
understanding of the notion creativity. Beginning from Antiquity to the Renaissance creative activity had
collective character. In the ХVІІ – ХVІІІ century creativity acts as means of individual perception and the
relation to collective experience which displays acquisition by creativity of character of individual activity. In
ХІХ and ХХ century aesthetics of individualism acts as the rights to freedom of creative activity which displays
free display of own understanding by the artist of creative process. The phenomenon of creativity is investigated
as a part of cultural process and is presented as socio–cultural phenomenon. В статье рассматривается проблематика феномена творчества в контексте
исторической динамики социокультурного развития (западноевропейский контекст). Внимание
акцентируется на оопределении творчества как способа поиска новых форм самовыражения
человеческой активности. Определяется, что творчество выступает в качестве формы взаимосвязи
между различными культурно–информационными каналами. В статті розглядається проблематика феномена творчості в контексті історичної
динаміки соціокультурного розвитку (західноєвропейський контекст). Увага акцентується на
визначенні творчості як засобу пошуку нових форм самовираження людської активності.
Визначається, що творчість виступає у якості форми взаємозв’язку між різноманітними культурно–
інформаційними каналами.